2015
DOI: 10.1111/tid.12352
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of intestinal dysbiosis in liver transplant candidates

Abstract: While the abundance of both Bifidobacterium and Enterococcus is related to liver dysfunction, the size of the Enterococcus population seems to be the most important determinant of pre-LT gut dysbiosis in cirrhotic patients. The H2 O2 -producing Lactobacillus strains potentially ameliorate this dysbiotic state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…investigated LT candidates and revealed that pre-LT dysbiosis was significantly correlated with Enterococcus 36 . Several other studies have also revealed that Enterobacteriaceae and Enterococcus were more abundant in LT candidates with liver cirrhosis than in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…investigated LT candidates and revealed that pre-LT dysbiosis was significantly correlated with Enterococcus 36 . Several other studies have also revealed that Enterobacteriaceae and Enterococcus were more abundant in LT candidates with liver cirrhosis than in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal microbial characterization and alteration in early phase and subsequent intestinal barrier dysfunction during acute rejection after LT have been reported [148][149][150][151][152][153]. Due to the high sensitivity of microbial changes during acute rejection after LT, intestinal microbial variation has been suggested to predict acute rejection in the early phase after LT [148].…”
Section: Gut Microbiota and Hepatic Ischemia Reperfusion In Liver Surmentioning
confidence: 99%
“…Enterobacteriaceae species have been reported to be associated with higher MELD scores, whereas the Ruminococcaceae species have been associated with lower MELD scores[ 56 ]. A study of the IM in patients with advanced liver disease revealed that decreased abundance of Bifidobacterium and increased abundance of Enterococcus were associated with increasing liver dysfunction[ 59 ]. The term “cirrhosis dysbiosis ratio” was coined to describe the ratio of autochthonous taxa (taxa that are benign and usually present in the gut such as Ruminococcaceae , Lachnospiraceae , and Clostridiales ) to non-autochthonous ones ( Enterobacteriaceae and Bacteroidaceae ).…”
Section: Characterization Of Im In Cirrhosismentioning
confidence: 99%